Collapse susceptibility mapping using srtm data obtained from topodata project - Lollo, José Augusto [UNESP]; Cabrera, Jaime M. [UNESP]; Curti, Juliano Suman [UNESP] (Springer Nature, 2015)
The occurrence of collapsible soils and collapse processes due to disruptions in water and sewage networks is the main urban environmental problem concerning material losses in many cities of southeastern Brazil. This work shows how expeditious evaluations based on the relationship between relief and soil profiles performed using SRTM (Shuttle Radar Topography Mission) sensor information enable evaluating the collapse susceptibility of urban areas. The land elements were identified and classified using algebra maps from steepness, horizontal curvature and vertical curvature attributes. This combination allowed elaborating a Land Elements Chart which resulted in ten land elements, of which three had morphometric and morphogenetic characteristics able to provide soils with important collapsibility potential. Data from field investigation and laboratory tests where used to describe the collapsible potential of soils. Results showed that the land elements that combine convex vertical curvature with divergent horizontal curvature and steepness less than 10% presents soil profiles composed of soft sandy textured soils (at least 70% of sand, void ratio higher than 0.8) and soil layer thicknesses higher than 10 m with SPT index values less than six blow counts showing high collapse potential.
Keywords: Collapse Potential; Problematic Soils; Soil Collapse; Terrain Evaluation